a guide to sources and instruments for external growth - "Lajoux, Alexandra Reed"; "Weston, Fred J" (New York, 1999)
"Contents: Part 1: Prerequisites -- Chapter 1: Basic definitions and data -- Chapter 2: Assessing financing needs -- Chapter 3: Regulatory, tax and accounting issues in structuring deal financing -- Part 2: A closer look at instruments -- Chapter 4: Dynamics of debt-based financing -- Chapter 5: Dynamics of equity-based financing -- Chapter 6: Dynamics of ""Hybrid"" financing -- Part 3: A closer look at sources -- Chapter 7: Working with debt sources -- Chapter 8: Working with equity sources -- Chapter 9: Working with ""Backers"" -- Part 4: Strategies for financing and refinancing -- Chapter 10: Managing multiple sources -- Chapter 12: Refinancing strategies -- Part 5: Global issues: Macro/Micro/Tax -- Chapter 13:Macroeonomic aspects of global M&A financing -- Chapter 14: Microeconomic aspects of global M&A financing -- Chapter 15: International financing: Tax fine points -- Conclusion : M&A financing and refinancing: instruments for successful growth."
includes index
Keywords: Consolidation and merger of corporations